STEM-Integrated PBL: Enhancing Science Literacy and Skills in Light Wave Material - Kusumaningtyas, Dian Artha; Leni, Leni; Toifur, Moh (Jurnal Penelitian Pembelajaran Fisika, 2024)
This study looked for the influence and effectiveness of STEM-integrated PBL implementation on scientific literacy skills. The research method is quasi-experimental design, as described by Manova. The results obtained are: 1) there is an effect of implementing STEM-integrated PBL on scientific literacy skills in the domain of knowledge and skills with sig. = 0.000; 2) there is an effect of STEM-integrated PBL implementation on scientific literacy skills in the knowledge domain, with sig.= 0.000 content aspect, sig.= 0.000 procedural aspect, and sig.= 0.000 apistermic aspect; 3) there is an effect of implementing STEM-integrated PBL on scientific literacy skills in the skill domain, with sig.= 0.002 aspects of explaining natural phenomena, sig.= 0.001 aspects of designing, evaluating investigations, and sig.= 0.000 aspects of interpreting data, scientific evidence; 4) The implementation of STEM-integrated PBL is quite effective in increasing scientific literacy in the domain of knowledge and skills with an N-gain of 59% and 58%.